Multimodal management of solitary axillary lymph node metastasis from a recurrent nasopharyngeal undifferentiated carcinoma: a case report and review of the literature - Mansouri, Houyem; Zemni, Ines; Hssine, Samia Ben; Boukhris, Sabrine; Achouri, Leila; Mahjoub, Najet (Frontiers in Oncology, 2025)
IntroductionUndifferentiated Nasopharyngeal carcinoma (UNPC) exhibits the highest loco-regional cervical lymph node recurrence among head and neck epithelial malignancies. Axillary lymph node recurrence in NPC is uncommon.Case descriptionA 44-year-old male presented with two-month history of painless swelling of the right axilla. He was diagnosed with stage IVB UNPC three years and eight months previously and had undergone neoadjuvant chemotherapy, and concurrent chemo-radiotherapy. Biopsy of the axillary swelling revealed metastatic UNPC. The patient was treated with axillary lymph node dissection followed by chemotherapy, and right axillary radiotherapy. Currently, the patient has been disease free for 12 months.ConclusionTo our knowledge, this is the second reported case of UNPC with isolated axillary lymph node recurrence after remission, treated with axillary lymph node dissection, chemotherapy, and radiotherapy. This case highlights a rare pattern of metastasis and underscores the need for thorough investigations and imaging in the long-term follow-up of NPC.